2019
DOI: 10.1016/j.jhep.2019.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of genomic analysis in adults with idiopathic liver disease

Abstract: Background & Aims: Adult patients suffering from liver disease of unknown cause represent an understudied and underserved population. The use of whole-exome sequencing (WES) for the study of a broader spectrum of non-oncological diseases, among adults, remains poorly studied. We assessed the utility of WES in diagnosis and management of adults with unexplained liver disease despite comprehensive evaluation by a hepatologist and with no history of alcohol overuse. Methods: We performed WES and deep phenotyping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
90
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 27 publications
2
90
0
1
Order By: Relevance
“…However, the absence of positive family history should not deter any physician from pursuing genomic analysis if any of the other features are present. In fact, in our series, none of the 5 adult patients with idiopathic liver disease who attained a genetic diagnosis reported a family history of liver disease. Lastly, as WES is getting more widely used in clinical practice, it is already replacing the conventional single‐gene and gene‐panel tests in large academic centers.…”
Section: When Should Wes Be Used In Adult Hepatology Clinical Practice?mentioning
confidence: 59%
See 4 more Smart Citations
“…However, the absence of positive family history should not deter any physician from pursuing genomic analysis if any of the other features are present. In fact, in our series, none of the 5 adult patients with idiopathic liver disease who attained a genetic diagnosis reported a family history of liver disease. Lastly, as WES is getting more widely used in clinical practice, it is already replacing the conventional single‐gene and gene‐panel tests in large academic centers.…”
Section: When Should Wes Be Used In Adult Hepatology Clinical Practice?mentioning
confidence: 59%
“…As an example, hemochromatosis could be due to loss‐of‐function mutations in five distinct genes, namely HFE , HJV , HAMP , TFR2 and SLC40A1, but only HFE gene is typically sequenced. In a recent study of 19 patients with idiopathic liver disease, despite a comprehensive work‐up performed by a hepatologist, WES provided a genetic diagnosis in 5 of these patients (about 25%), uncovering four distinct monogenic disorders . This study identified 5 patients with up to 2 decades of misdiagnosis who in fact harbored Mendelian disorders previously unrecognized and highlight the utility of WES in patients with undiagnosed liver disease.…”
Section: Where Could Hepatologists Be Missing Liver‐related Genetic Tmentioning
confidence: 90%
See 3 more Smart Citations